A rare functional haplotype of the P2RX4 and P2RX7 genes leads to loss of innate phagocytosis and confers increased risk of age‐related macular degeneration. Issue 4 (9th January 2013) - Gu, Ben J.; Baird, Paul N.; Vessey, Kirstan A.; Skarratt, Kristen K.; Fletcher, Erica L.; Fuller, Stephen J.; Richardson, Andrea J.; Guymer, Robyn H.; Wiley, James S.
Abstract : Age‐related macular degeneration (AMD) is a leading cause of blindness in Western countries and is diagnosed by the clinical appearance of yellow subretinal deposits called drusen. Genetic changes in immune components are clearly implicated in the pathology of this disease. We have previously shown that the purinergic receptor P2X7 can act as a scavenger receptor, mediating phagocytosis of apoptotic cells and insoluble debris. We performed a genetic association study of functional polymorphisms in the P2RX7 and P2RX4 genes in a cohort of 744 patients with AMD and 557 age‐matched Caucasian control subjects. The P2X4 Tyr315Cys variant was 2‐fold more frequent in patients with AMD compared to control subjects, with the minor allele predicting susceptibility to disease. Pairwise linkage disequilibrium was observed between Tyr315Cys in the P2RX4 gene and Gly150Arg in the P2RX7 gene, and these two minor alleles formed a rare haplotype that was overrepresented in patients with AMD ( n =17) compared with control subjects ( n =3) (odds ratio 4.05, P =0.026). Expression of P2X7 (wild type or variant 150Arg) in HEK293 cells conferred robust phagocytosis toward latex beads, whereas coexpression of the P2X7 150Arg with P2X4 315Cys variants almost completely inhibited phagocytic capacity. Fresh human monocytes harboring this heterozygous 150Arg‐315Cys haplotype showed 40% reduction in bead phagocytosis. In the primate eye, immunohistochemistry indicated that P2X7 and P2X4 receptors were coexpressed on microglia and macrophages, but neither receptor was seen on retinal pigment epithelial cells. These results demonstrate that a haplotype including two rare variants in P2RX7 and P2RX4 confers a functional interaction between these two variant receptors that impairs the normal scavenger function of macrophages and microglia. Failure of this P2X7‐mediated phagocytic pathway may impair removal of subretinal deposits and predispose individuals toward AMD.—Gu, B. J., Baird, P. N., Vessey, K. A., Skarratt, K. K., Fletcher, E. L., Fuller, S. J., Richardson, A. J., Guymer, R. H., Wiley, J. S. A rare functional haplotype of the P2RX4 and P2RX7 genes leads to loss of innate phagocytosis and confers increased risk of age related macular degeneration. FASEB J. 27, 1479–1487 (2013). www.fasebj.org